“Covid – 19 Revisited” With Ocular Manifestations - Raunaq Poonia; Anju Kochar (Delhi Journal of Ophthalmology)
In December 2019, a novel corona virus (CoV) pandemic, caused by the severe acute respiratory syndrome corona virus–2 (SARS-CoV-2) emerged from China. This virus causes the corona virus disease 2019 (COVID-19). The ocular implications of human CoV infections have not been widely studied. There are few reports on the association of severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) with ocular abnormalities. Understanding ocular manifestations of patients with COVID-19 by ophthalmologists and others may facilitate the diagnosis and prevention of transmission of the disease. The review article will also highlight CoVs and their associated ocular infections. We hope that this article will serve as further research into the ocular implications of human CoV infections. As the current pandemic continues, a better understanding of the virus will emerge, hopefully with more emphasis on research into the relationship between human CoVs and the eye. This understanding will not only help us to guide infection control measures but can also provide insights on the feasibility of using ocular tissue or even tears as a medium of diagnosis. Meanwhile, ophthalmologists and other health-care workers should continue to work on the side of caution and continue to prevent the possible transmission of CoVs through ocular tissue.